Highly efficient organic solar cells based on a simple polymer donor derived from a difluorinated benzene-quarterthiophene skeleton - Zhang, Zesheng; Kong, Lingchen; Liu, Chao; Tang, Hua; Wang, Xinkang; Chen, Mingqing; Luo, Mei; Zhang, Lianjie; Liu, Cheng; Liu, Xuncheng; Ma, Dongge; Brabec, Christoph; et al. (Journal of Materials Chemistry C, 2025)
Conjugated polymers with simple chemical structures are essential for the commercialization of organic solar cells (OSCs). However, a simplicity-performance dilemma arises, as current design principles often result in an inverse correlation between these two factors, significantly hindering the commercialization of OSCs. In this study, we investigated the impact of fluorine substitution positions on benzene rings within polythiophenes (PTs), leading to two polymers composed of non-fused rings of o-difluorobenzene-quarterthiophene and p-difluorobenzene-quarterthiophene, namely, Po2F and Pp2F. The Po2F/Y6BO devices achieved a remarkable efficiency of 15.45%, with the active layer fabricated via layer-by-layer (LBL) spin coating, significantly surpassing the Pp2F/Y6BO blend (12.14%) and ranking among the top-performing oligothiophene-based OSCs. The enhancement is mainly attributed to improved phase separation, reduced exciton lifetimes, and suppressed mixing compatibility with Y6BO of Po2F, compared to Pp2F. In addition, the simple polymer Po2F demonstrated a much higher figure of merit (FOM) in chemical accessibility than polymers with fused rings, indicating its great potential for cost reduction. Beyond its role as a donor, Po2F also enhanced the efficiency of PM6:L8BO from 17.74% to 19.05% and extended T80 from 239 to 377 hours when used as an interlayer between the PEDOT:PSS buffer layer and the active layer. This study highlights the significance of a polymer donor-based non-fused ring towards commercially viable OSCs and offers valuable insights for designing high-performance polymers.
CRIS-Team Scopus Importer:2025-04-01